2003
DOI: 10.1177/0743558403255070
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Parental Support, Behavioral Control, and Psychological Control on the Academic Achievement and Self-Esteem of African American and European American Adolescents

Abstract: The purpose of this study was to examine the relationships between adolescent functioning (i.e., self-esteem and academic achievement) and parental support, behavioral control, and psychological control in European American and African American adolescents. Hierarchical regression analyses indicated that supportive behaviors of African American mothers toward their adolescent children positively predicted both self-esteem and academic achievement. Psychological control was significantly related to adolescent s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
217
2
10

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 266 publications
(244 citation statements)
references
References 56 publications
(88 reference statements)
15
217
2
10
Order By: Relevance
“…These questions were based on a review of the relevant research literature (Bean, Bush, McKenry & Wilson, 2003;Buddy, 2007;Buhs & Ladd, 2001;Diaz, 2003;Eamon, 2005;Oliverez & Tierney, 2005;Turner, Chandler & Heffer, 2009).…”
Section: Participans and Proceduresmentioning
confidence: 99%
“…These questions were based on a review of the relevant research literature (Bean, Bush, McKenry & Wilson, 2003;Buddy, 2007;Buhs & Ladd, 2001;Diaz, 2003;Eamon, 2005;Oliverez & Tierney, 2005;Turner, Chandler & Heffer, 2009).…”
Section: Participans and Proceduresmentioning
confidence: 99%
“…These studies have focused on school success related to academic performance and achievement and academic motivation or orientation (Bean et al, 2003;Bush et al, 2002;Chen et al, 1997;Chen et al, 2000;Ingoldsby, Schvanevldt, Supple, & Bush, 2003;Kim, Brody, & Murry, 2003;Laible & Carlo, 2004;McBride-Chang & Chang, 1998). Parents' responsive attitudes and adequate control facilitate adolescents' autonomous behaviors and encourage adolescents to solve problems independently and actively (Aunola, Stattin, & Nurmi, 2000).…”
Section: Fathers and Adolescent Academic Developmentmentioning
confidence: 99%
“…For example, mothers' warm behavior enhanced more adaptive school functioning of adolescents than fathers' behavior did, whereas mothers' hostile behavior had a more deleterious association with academic outcomes than fathers' hostile behavior did (Grolnick, Ryan, & Deci, 1991;Repinski & Shonk, 2002;Russell & Russell, 1987). However, some studies have found differences in adolescent perceptions of maternal and paternal parenting characteristics and emphasized the unique influence of fathers on academic outcomes (Amato & Fowler, 2002;Ang, 2006;Bean et al, 2003;Bean, Barber, & Crane, 2006;Heaven & Newbury, 2004;Kenny & Gallagher, 2002;Kim & Rohner, 2002;Laible & Carlo, 2004;Plunkett & Bámaca-Gómez, 2003;Shek et al, 1998;Supple & Small, 2006). For instance, even though both fathers and mothers were perceived to be warm and affective, fathers relatively were harsher and less responsive than mothers were (Ang, 2006;Bean et al, 2006;Kenny & Gallagher, 2002;Kim & Rohner, 2002;Shek, 1998;Supple & Small, 2006).…”
Section: Fathers and Adolescent Academic Developmentmentioning
confidence: 99%
See 2 more Smart Citations